Clickable photoaffinity ligands for the human serotonin transporter based on the selective serotonin reuptake inhibitor (S)-citalopram. Issue 21 (15th November 2018) - Yarravarapu, Nageswari; Geffert, Laura; Surratt, Christopher K.; Cascio, Michael; Lapinsky, David J.
Graphical abstract: Abstract: To date, the development of photoaffinity ligands targeting the human serotonin transporter (hSERT), a key protein involved in disease states such as depression and anxiety, have been radioisotope-based (i.e., 3 H or 125 I). This letter instead highlights three derivatives of the selective serotonin reuptake inhibitor (SSRI) ( S )-citalopram that were rationally designed and synthesized to contain a photoreactive benzophenone or an aryl azide for protein target capture via photoaffinity labeling and a terminal alkyne or an aliphatic azide for click chemistry-based proteomics. Specifically, clickable benzophenone-based ( S )-citalopram photoprobe6 (hSERT K i = 0.16 nM) displayed 11-fold higher binding affinity at hSERT when compared to ( S )-citalopram (hSERT K i = 1.77 nM), and was subsequently shown to successfully undergo tandem photoaffinity labeling-biorthogonal conjugation using purified hSERT. Given clickable photoprobes can be used for various applications depending on which reporter is attached by click chemistry subsequent to photoaffinity labeling, photoprobe6 is expected to find value in structure-function studies and other research applications involving hSERT (e.g., imaging).